Optimality and Duality for Multiobjective Fractional Programming Involving Nonsmooth Generalized (ℱ,b,ϕ,ρ,θ)-Univex Functions - Jen-Chwan Liu; Chun-Yu Liu (International Journal of Mathematics and Mathematical Sciences)
We establish properly efficient necessary and sufficient optimality conditions for multiobjective fractional programming involving nonsmooth generalized (ℱ,b,ϕ,ρ,θ)-univex functions. Utilizing the necessary optimality conditions, we formulate the parametric dual model and establish some duality results in the framework of generalized (ℱ,b,ϕ,ρ,θ)-univex functions.